Acetylation modulates thyroid hormone receptor intracellular localization and intranuclear mobility. (15th September 2019) - Anyetei-Anum, Cyril S.; Evans, Rochelle M.; Back, Amanda M.; Roggero, Vincent R.; Allison, Lizabeth A.
Abstract: The thyroid hormone receptor (TR) undergoes nucleocytoplasmic shuttling, but is primarily nuclear-localized and mediates expression of genes involved in development and homeostasis. Given the proximity of TR acetylation and sumoylation sites to nuclear localization (NLS) and nuclear export signals, we investigated their role in regulating intracellular localization. The nuclear/cytosolic fluorescence ratio (N/C) of fluorescent protein-tagged acetylation mimic, nonacetylation mimic, and sumoylation-deficient TR was quantified in transfected mammalian cells. While nonacetylation mimic and sumoylation-deficient TRs displayed wild-type N/C, the acetylation mimic's N/C was significantly lower. Importins that interact with wild-type TR also interact with acetylation and nonacetylation mimics, suggesting factors other than reduced importin binding alter nuclear localization. FRAP analysis showed wild-type intranuclear dynamics of acetylation mimic and sumoylation-deficient TRs, whereas the nonacetylation mimic had significantly reduced mobility and transcriptional activity. Acetyltransferase CBP/p300 inhibition enhanced TR's nuclear localization, further suggesting that nonacetylation correlates with nuclear retention, while acetylation promotes cytosolic localization. Highlights: The thyroid hormone receptor (TR) undergoes nucleocytoplasmic shuttling. We examine the impact of acetylation on localization and intranuclear dynamics. Coimmunoprecipitation, FRAP, and transcription assays were performed in cells. Nonacetylation mimics show reduced gene transactivation and intranuclear mobility. Acetylation mimics show enhanced gene transactivation and cytosolic localization.